Does the route of administration matter? Systematic review and meta-analysis of randomized clinical trials between vaginal versus intramuscular progesterone administration in the prevention of preterm birth - Galdos-Bejar, Marcelo (2024)
Objective. To determine the effectiveness of intramuscular progesterone compared to vaginal application in the prevention of asymptomatic preterm birth (PTB) in randomized clinical trials. Materials and Methods. A systematic search of electronic databases (Embase, PubMed and Scopus) was performed. Randomized clinical trials comparing vaginal and Intramuscular progesterone (17-OHPC) in pregnant women at high risk of PTB. Additionally, bias and certainty assessment were performed. Results. Six clinical trials with a total of 1,408 randomized patients were included. The reported incidence of PTB < 37 weeks ranged from 10.9% to 43.9% for vaginal progesterone, and 14.0% to 38% for 17-OHPC. At the time of meta-analysis, patients receiving 17-OHPC was associated with a lower incidence of PTB < 28 weeks than vaginal use (Risk Difference 0.14; CI 0.01-0.29; I2 = 83.9%; T2 = 0.02) with no significant difference in differences in PTB < 37 and < 34 weeks. Additionally, on neonatal outcomes, the most common was admission to the neonatal ICU independent of the method of administration (6.1% and 7.7%), followed by APGAR < 7 (4.1% and 5.2%), with no significant differences in neonatal outcomes. Conclusions. Both the use of vaginal progesterone and 17-OHPC in the prevention of PTB in singleton high-risk gestations are reasonable options, with similar incidence of PTB and no additional impact on short-term neonatal complications. Thus, costs, resource availability and patient preferences should be considered when choosing a route of administration.